THE IMPACT OF HEAVY MENSTRUAL BLEEDING (MENORRHAGIA) AND IRON STATUS IN EXERCISING FEMALES. Issue 4 (1st February 2017) - Bruinvels, Georgie; Burden, Richard J; Cushway, Timothy; Brown, Nicola; Pedlar, Charles; Richards, Toby
Abstract : Background: The effects of the menstrual cycle on exercise participation and performance are poorly researched. Menstrual blood loss is a leading cause of iron deficiency (ID) and ultimately iron deficiency anaemia (IDA). Furthermore, iron losses are increased in those who exercise. The menstrual cycle, ID and IDA may affect the ability to exercise, mood state, productivity and quality of life while also increasing fatigue and anxiety. Objective: To determine the impact of heavy menstrual bleeding (HMB) on iron status; to identify the association between HMB, ID and IDA with self-reported exercise training and performance. Design: A cross-sectional study design was used. Setting: Routine healthcare assessments in Singapore. Participants: Healthy females (n=271; mean age 36.3±9.6 years, body mass 58.3±12.5 kg, height 1.59±0.12 m). Inclusion criteria: regularly menstruating and reporting >60 minutes exercise participation per week or 'taking part in races, in a relatively non-competitive manner'. Interventions: No interventions were applied. Main Outcome Measurements: Participants completed a 'Female Health Questionnaire' capturing: a 4-part diagnostic criteria for HMB; aspects of exercise training habits and performance; exercise volume; and competition level. Haemoglobin concentration ([Hb]) and serum ferritin were measured in all participants. Results: 22.4% reported HMB, 18.8% had IDA ([Hb]<12 g/dL), 30.0% severe ID (ferritin<16 ug/L), and 48.0% had moderate ID (ferritin <30 ug/L). Those with HMB were twice as likely to suffer IDA or have moderate ID, while they were nearly three times as likely to have severe ID ( p<0.05 ). When controlling for IDA those with HMB were 3.9 times more likely to cite negative impacts on training and performance as a result of the menstrual cycle ( p<0.05 ). Conclusions: Heavy menstrual bleeding is common in exercising women. Regular screening should be encouraged to check iron status as this has potential to cause IDA in addition to compromising exercise training behaviours and performance.